A New Prime Code for Synchronous Optical Code Division Multiple-Access Networks. (28th February 2018) - Abbas, Huda Saleh; Gregory, Mark A.; Austin, Michael W.
Abstract : A new spreading code based on a prime code for synchronous optical code-division multiple-access networks that can be used in monitoring applications has been proposed. The new code is referred to as "extended grouped new modified prime code." This new code has the ability to support more terminal devices than other prime codes. In addition, it patches subsequences with "0s" leading to lower power consumption. The proposed code has an improved cross-correlation resulting in enhanced BER performance. The code construction and parameters are provided. The operating performance, using incoherent on-off keying modulation and incoherent pulse position modulation systems, has been analyzed. The performance of the code was compared with other prime codes. The results demonstrate an improved performance, and a BER floor of 10 −9 was achieved.